Perlindungan Hukum Hak Cipta Tari Pendet Menurut Undang-Undang Nomor 28 Tahun 2014 - Ni Putu Epy Nariasih; Ni Luh Mahendrawati; Ida Ayu Putu Widiati (Fakultas Hukum Universitas Warmadewa, 2021)
The country of Indonesian has a variety of cultures that cause the tourism industry to develop very rapidly; often many Indonesian cultures are claimed by other countries. Related to this there are two main problems, namely: 1. how is protection of Pendet Dance copyright violations according to Law Number 28 of 2014? The research used is normative legal research with a statutory approach. The result of the study shows that Pendet art is a cultural heritage that needs to be protected. Copyright legal protection for Pendet dance in the legal protection that can be given is, namely conducting an inventory and documentary by compiling a database. Legal protection is given ina repressive and preventive manner. Repressive legal protection, namely legal protection efforts carried out by the state if there are claims from other countries on folklore in Indonesia, therefore the inventory and documentary effort that have been compiled in the database by the authorized ministry to do so. Copyright legal protection for folklore, especially in pendet dance in Indonesian is still not optimal. Namely by preservation and continue to introduce pendet dance folklore to the wider community for the richness of traditional culture owned by the Indonesian state. Legal consequences that can be made if there has been a copyright violation, then the enforcement of copyright law can be pursued through two paths. Namely the civilian route by filing civil lawsuits and criminal lines with criminal charges.